1998
DOI: 10.1002/(sici)1097-0215(19980717)77:2<251::aid-ijc14>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD3-based bispecific antibody designed for therapy of human B-cell malignancy can induce T-cell activation by antigen-dependent and antigen-independent mechanisms

Abstract: Anti‐CD3 × anti‐B‐cell antigen bispecific monoclonal antibodies (bsAbs) can redirect T‐cell‐mediated lysis toward malignant B cells. Clinical trials with CD3‐based bsAbs have shown toxicity in patients which is likely related to non‐specific T‐cell activation and targeting. Our current studies were designed to explore the mechanisms responsible for the observed in vivo toxicity by evaluating the immunologic effects of 2 different bsAb preparations in vitro. 1D10 was used as the tumor specific arm of the bsAbs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Overall, our findings demonstrate that bsAb constructs containing the CD3 binding domain and a functional Fc domain can specifically crosslink T cells with FcR-positive immune cells, resulting in the activation of T cells in an antigen-independent manner. This observation is consistent with previous preclinical reports [34;35] , including safety data from a clinical trial with ertumaxomab, an IgG-version bsAb with a functional Fc domain, in which nearly all the patients developed symptoms of CRS [36] . Nonetheless, the reduced nonspecific activity of Tetra-IgG (Fc null) suggests that a mutational approach can potentially improve the safety of IgG-like bsAbs.…”
supporting
confidence: 92%
“…Overall, our findings demonstrate that bsAb constructs containing the CD3 binding domain and a functional Fc domain can specifically crosslink T cells with FcR-positive immune cells, resulting in the activation of T cells in an antigen-independent manner. This observation is consistent with previous preclinical reports [34;35] , including safety data from a clinical trial with ertumaxomab, an IgG-version bsAb with a functional Fc domain, in which nearly all the patients developed symptoms of CRS [36] . Nonetheless, the reduced nonspecific activity of Tetra-IgG (Fc null) suggests that a mutational approach can potentially improve the safety of IgG-like bsAbs.…”
supporting
confidence: 92%
“…Some tumor in®ltration by leukocytes has been seen following MDX-210 therapy (Link et al, 1998), and we have observed the induction of tumor in®ltration by leukocytes in several patients treated with 2B1. However, there is no consistent, profound leukocyte in®ltration of tumor following BsAb therapy, and preclinical data suggest that BsAb promoted cytotoxicity will require eector to target ratios of at least 1 : 1 for successful therapy (Weiner et al, 1993b).…”
Section: Importance Of Tumor Inflammation For Effective Bispecific Anmentioning
confidence: 53%
“…2B1-promoted antigen presentation led to the induction of anti-HER2/neu antibodies, but only in patients treated with 2B1 doses exceeding the ultimate MTD (Clark et al, 1997). Taken together, these results indicate that whole IgG BsAb targeting eector cell trigger molecules are unsuitable therapeutic structures, in accord with predictions in selected preclinical murine models (Link et al, 1998). The engagement of T cell receptor V b chains and MHC Class II by the bacterial superantigen, staphylococcal enterotoxin A (SEA), also leads to profound leukocyte activation and the attendant dose-limiting toxicity of a multi-speci®c fusion protein consisting of an anti-tumor Fab fragment and SEA (Giantonio et al, 1997;Alpaugh et al, 1998).…”
Section: Clinical Toxicities Of Bispecific Antibodiesmentioning
confidence: 75%
“…The relative lack of specificity currently presents a major obstacle for the wider implementation of powerful immunotherapeutic agents such as chimeric antigen receptors and bispecific antibodies (57)(58)(59)(60). In this context, specific somatic mutations that alter the encoded proteins of cancer driver genes represent biochemical features that distinguish cancer cells from normal cells in unparalleled fashion.…”
Section: Discussionmentioning
confidence: 99%